2010
DOI: 10.1007/s12630-010-9274-8
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing anesthesia medication drawers using human factors and quality assurance methods

Abstract: Purpose In Calgary, each of the three acute-care adult hospitals had different anesthetic medication carts with their own type and layout of anesthetic medications. A number of anesthesiologists moved among the different sites, increasing the potential for medication errors. The objective of this study was to identify the anesthetic medications to include and to determine how they should be grouped and positioned in a standardized anesthesia medication cart drawer. Methods A standardized list of medications wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Agarwal et al (2005) conducted a study on pediatric code carts and found that having medications systematically organized (i.e., designed to facilitate their identification, use, and replacement) reduced medication retrieval times when compared to baseline drawers. Schultz et al (2010) collected feedback from relevant health care personnel and determined standardization, grouping of like medications, and organizing based on frequency of use were the most important factors to consider during code cart redesign; however, no formal testing was conducted. Last, it has been concluded that humans' cognitive architecture consists of a limited working memory (Paas, Tuoviinen, Tabbers, & Van Gerven, 2003), which adds to the importance of these code cart organizational improvements since a well-organized code cart can reduce load on working memory.…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal et al (2005) conducted a study on pediatric code carts and found that having medications systematically organized (i.e., designed to facilitate their identification, use, and replacement) reduced medication retrieval times when compared to baseline drawers. Schultz et al (2010) collected feedback from relevant health care personnel and determined standardization, grouping of like medications, and organizing based on frequency of use were the most important factors to consider during code cart redesign; however, no formal testing was conducted. Last, it has been concluded that humans' cognitive architecture consists of a limited working memory (Paas, Tuoviinen, Tabbers, & Van Gerven, 2003), which adds to the importance of these code cart organizational improvements since a well-organized code cart can reduce load on working memory.…”
Section: Introductionmentioning
confidence: 99%
“…Medication errors are the single most common cause of malpractice cases against anesthesiologists in Canada and account for approximately two-thirds of all damages awarded [20]. Subsequent efforts to standardize labeling and organization of medication carts [21] address the risk of mistaken or mis-stocked medication vials. However, in a survey of Canadian Anesthesiologists' Society members, the majority of medication errors were attributed to “syringe swaps” (60%), rather than in misidentification (39%) or mis-stocking (18%) of ampoules/vials [22].…”
Section: Discussionmentioning
confidence: 99%
“…19 What More Can We Do? 21 We also need to standardize the doses that are used for medications such as epinephrine in irrigation and tumescent solutions. First, we should separate medications for adults, pediatric patients, and neonates.…”
Section: Preventing Medication Errorsmentioning
confidence: 99%
“…Other recommendations include n reviewing and revising code carts, which entails n stocking a separate pediatric code cart, n color coding the different drawers based on child size, 20 and n stocking a separate neonatal medication box for the code cart if neonates are treated in the facility; n providing medication reference sheets with IV titration dosing guides for all medications in all concentrations available; and n standardizing medication trays within the facility, including; n stocking the separate trays with appropriate doses for the patient receiving care and n standardizing medication trays across facilities in the geographical area to provide consistency for anesthesia professionals who work in more than one setting. 21 We also need to standardize the doses that are used for medications such as epinephrine in irrigation and tumescent solutions. When pharmacy personnel are available, they should mix medications under a hood if the medication is intended for use on the sterile field.…”
Section: Preventing Medication Errorsmentioning
confidence: 99%